Scientific foundations of clinical assessment - Haynes, Stephen N.; Smith, Greg (Gregory T.); Hunsley, John, 1959- (New York : Routledge, 2011)
'Scientific Foundations of Clinical Assessment is a user-friendly overview of the most important science-based principles and concepts of clinical assessment. It provides readers with a science-based framework for interpreting assessment research and making good assessment decisions, such as selecting the best instruments and measures, and interpreting the obtained assessment data. Written in a direct and highly readable fashion, this text is one every professional and graduate student needs'--
Includes bibliographical references and index.
Keywords: Psychological tests -- Methodology; Psychodiagnostics -- Methodology